SISTEMATIS REVIEW TENTANG PENGOBATAN TELEMEDICINE : EFEKTIVITAS, EFISIENSI, DAN KEPUASAN PASIEN - Anis Ansyori; Fita Rusdian Ikawati; Retno Dewi Prisusanti; Achmad Jaelani Rusdi; Lilik Afifah; Untung Slamet Suhariyono (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
Telemedicine, the use of digital technology and communication for remote healthcare services, has seen rapid development and offers potential improvements in accessibility and efficiency in healthcare services. However, the adoption and implementation of telemedicine also face various challenges, including data privacy and security, technological infrastructure readiness, and legal and regulatory barriers. This study aims to evaluate the effectiveness, efficiency, and patient satisfaction in the use of telemedicine based on existing scientific evidence. This study employs a systematic review methodology of related telemedicine studies. The results of this review are summarized and form the basis for further discussion about the effectiveness of telemedicine, challenges in its implementation, and its implications for the healthcare sector and further research. Recommendations are provided based on the findings of this review for future research or practice focusing on enhancing the effectiveness, efficiency, and patient satisfaction in the use of telemedicine and overcoming challenges in its implementation.